2019
DOI: 10.1108/nfs-12-2018-0347
|View full text |Cite
|
Sign up to set email alerts
|

The impact of raw fermented milk products on perceived health and mood among Dutch adults

Abstract: Purpose The purpose of this paper was to evaluate health conditions prior to and at least two months after the start of consuming raw fermented milk (RFM) products. Design/methodology/approach One-Item health score, 1-item immunity score, immune status (ISQ), mood, bowel and skin conditions were rated for the period prior and post switching to RFM products. A linear mixed model was used to evaluate the post to prior RFM health and mood scores, taking into account gender, location of living and health group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Of the sample, 35.1% were men, and 45.0% reported to have poor health before switching to consuming RFM products. After the dietary change to RFM significant improvements on health and mood scores were reported, and the strongest improvements were reported by participants from the “poor health” group (discussed in detail elsewhere [26]). The health improvements in the “poor health” group were accompanied by a significant reduction in ISQ scores, suggesting improved immune fitness (see Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the sample, 35.1% were men, and 45.0% reported to have poor health before switching to consuming RFM products. After the dietary change to RFM significant improvements on health and mood scores were reported, and the strongest improvements were reported by participants from the “poor health” group (discussed in detail elsewhere [26]). The health improvements in the “poor health” group were accompanied by a significant reduction in ISQ scores, suggesting improved immune fitness (see Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…To develop and validate the ISQ, five studies were conducted. The ISQ was implemented in two subsequent studies [25,26]. The seven studies (summarized in Figure 1) are detailed in following sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The items were scored on a scale ranging from 0 (absent) to 10 (extreme). The 11-point scale has successfully been used in previous research [ 30 , 31 ], which showed that single item visual analog scales are just as sensitive and reliable as full-scale construct assessments of mood states like depression [ 32 ], fatigue [ 33 ], or quality of life [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“… 2016 ), reduced risk of cardiovascular disease (Sonestedt et al . 2011 ), beneficial effects on metabolism (Fernandez and Marette 2018 ), and positive changes in health and mood (Baars 2019 ). High consumption of cultured milk lowered the risk of developing bladder cancer (Larsson et al .…”
mentioning
confidence: 99%